Gambaran Kesehatan Lingkungan Kerja pada Kantor Bupati dan Kantor DPRD Kabupaten Manggarai Timur - Herlina L.D. Miyati; Mustakim Sahdan; Soni Doke (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Offices can pose potential hazards that affect employee safety and health. In East Manggarai Regency, the Regent’s Office and the DPRD Office have yet to provide optimal working comfort, especially regarding environmental health. This study aims to describe the work environment health conditions in both offices. The research is descriptive observational and was conducted at both offices from June to July 2024. The study population includes office rooms: 7 units in the Regent’s Office and 6 units in the DPRD Office. Data collection tools included questionnaires and observation sheets. Results showed that in the Regent’s Office, 2 of 7 rooms (83%) met safety standards, while 5 rooms (50–66%) did not. In the DPRD Office, 2 rooms met standards (83%), while 4 rooms (16%) did not. Accessibility in both offices was poor (33–65%). Clean water access met standards in 7 rooms (80%) of the Regent’s Office and in 2 rooms (80%) of the DPRD Office. Toilet facilities were below standard in both offices (0–73%). Domestic solid waste management failed in the Regent’s Office (0%) but was adequate in DPRD's general (88%) and finance (75%) sections.